2020
DOI: 10.1002/aoc.5522
|View full text |Cite
|
Sign up to set email alerts
|

Co/Cu bimetallic ZIF as New heterogeneous catalyst for reduction of nitroarenes and dyes

Abstract: Nowadays one of the great challenges is to design new bimetallic catalysts with enhanced catalytic activity, selectivity and recycling properties. In this work, the preparation of new Co/Cu bimetallic Zeolitic Imidazolate Framework (Co‐Cu/ZIF) as an efficient catalyst for the reduction of nitro compounds and organic dyes is described. Co‐Cu/ZIF was characterized with different techniques such as SEM, TEM, XRD, XPS, TGA, FT‐IR and UV–vis absorption indicating formation of entirely uniform cubic particles. Using… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 72 publications
1
17
0
4
Order By: Relevance
“…The results demonstrated that the synthesized CuCo-ZIFs had relatively uniform cubic particles. This was consistent the previous result of Gholinejad et al (2020). Moreover, the Brunauer-Emmett-Teller surface areas of CuCo-ZIFs were achieved approximately 1172 m 2 /g, while its Langmuir surfaces areas were achieved approximately 1907 m 2 /g.…”
Section: Figure 2 Edx Spectrum Of Cuco-zifssupporting
confidence: 92%
See 1 more Smart Citation
“…The results demonstrated that the synthesized CuCo-ZIFs had relatively uniform cubic particles. This was consistent the previous result of Gholinejad et al (2020). Moreover, the Brunauer-Emmett-Teller surface areas of CuCo-ZIFs were achieved approximately 1172 m 2 /g, while its Langmuir surfaces areas were achieved approximately 1907 m 2 /g.…”
Section: Figure 2 Edx Spectrum Of Cuco-zifssupporting
confidence: 92%
“…Notably, the position 421.36 cm -1 and 423.97 cm -1 correspondings to ZIF-67 and CuCo-ZIFs were the oscillation position of the metal-N bond. It means that the CuCo-ZIFs material completely achieved the desired crystal structure (Gholinejad et al, 2020).…”
Section: Figure 2 Edx Spectrum Of Cuco-zifsmentioning
confidence: 98%
“…The value of η depends on the optical transition type of the semiconductor photocatalyst, and η = 1 for the systems in our study because ZIF-67 is indirect band gap semiconductor. 45 The introduction of copper changed the sample from purple to blue purple. The approximative band gaps of ZIF-67, Co 8 Cu 2 -ZIF were 1.925 eV and 1.921 eV.…”
Section: Resultsmentioning
confidence: 99%
“…Copper-free heterogeneous palladium systems for this transformation have also been investigated. 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 Despite the many recent advances in heterogeneous Sonogashira reactions, high loadings of catalysts are required, and there are few examples involving low loadings of catalyst. Therefore, the development of effective heterogeneous catalysts that are active at low loadings in the Sonogashira reactions is highly desirable for realizing green sustainable organic transformations.…”
Section: Table 1 Optimization Of the Reaction Condition...mentioning
confidence: 99%